Wetting and interfacial phenomena in Ni-Cr-Hf/sapphire systems. Issue 2 (February 2020) - Valenza, Fabrizio; Sobczak, Natalia; Sobczak, Jerzy; Nowak, Rafal; Muolo, Maria Luigia; Passerone, Alberto; Sitzia, Saverio; Cacciamani, Gabriele
Abstract: The wetting of Ni-Hf and Ni-Cr-Hf alloys on sapphire has been studied in this work. Sapphire represents a "simple" and ideal case adopted for better understanding the basic phenomena involved in liquid/solid contact during casting of Ni-based superalloys. Wettability tests were performed by means of the sessile drop method at 1500 °C; moreover, after a certain time of liquid/solid contact, the liquid drop was pushed out from the substrate in order to open the interface and to investigate what happened at the interface. The characterization was performed by SEM/EDS and confocal microscopy in order to check the final interfacial structure. The results are discussed in terms of chemical interactions and by means of ad-hoc calculated phase diagrams. Hf present in Ni-based melts strongly reacted with sapphire forming HfO2 layers and inclusions; on the other hand, Cr decreased the contact angles of Ni melts without forming interfacial layers during liquid/solid contact.